18x-14=16x-13

Simple and best practice solution for 18x-14=16x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18x-14=16x-13 equation:


Simplifying
18x + -14 = 16x + -13

Reorder the terms:
-14 + 18x = 16x + -13

Reorder the terms:
-14 + 18x = -13 + 16x

Solving
-14 + 18x = -13 + 16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16x' to each side of the equation.
-14 + 18x + -16x = -13 + 16x + -16x

Combine like terms: 18x + -16x = 2x
-14 + 2x = -13 + 16x + -16x

Combine like terms: 16x + -16x = 0
-14 + 2x = -13 + 0
-14 + 2x = -13

Add '14' to each side of the equation.
-14 + 14 + 2x = -13 + 14

Combine like terms: -14 + 14 = 0
0 + 2x = -13 + 14
2x = -13 + 14

Combine like terms: -13 + 14 = 1
2x = 1

Divide each side by '2'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| 6-(3-8)= | | (x^3)+2x-m=0 | | 6n-10=2n+26 | | v/8=9 | | (8y-7)+(6x+4)+73=180 | | 5a+95=a+43 | | -(6-3v)=10+7v | | A+43=5a+95 | | (-6)(-2)(5)= | | -4x+45=-35 | | S=5s-64 | | 7s-85=5s-64 | | 97+(-4)= | | 2y+27=y+31 | | 6-6y+6y-8= | | 9+r+y+8=50 | | 4w+11=3w+17 | | 10=11(k-7) | | 4u-51=5u-75 | | -2(-3x-5)=-4x | | (x^3+x^2+x+1)*(11x-7)= | | 9+y+5=30 | | 10=15(x-4) | | K/9=-3 | | 7z=4z+3 | | 12=(N+4) | | -2(6+5n)=28-2n | | 4x+12=2(x+12) | | 15=a-326 | | 10=7(n+5) | | 4/3*(6y) | | 13+g=15 |

Equations solver categories